UK trade and productivity across space - Gio Mion; Dongzhe Zhang (Centre for Inclusive Trade Policy (CITP), University of Sussex Business School, 2025)
We revisit the presence of international trade activity premia at the firm-level, as well as the presence of agglomeration economies, for the UK over the period 2008-2017. In doing so, we also look at the nexus between agglomeration economies and international trade premia and in particular at whether these two phenomena complement or substitute each other. In other words, are international trade premia higher (lower) in denser places and if so what is the direction of causality? Our analysis indicates that premia are (especially for export) lower and in particular in denser areas there is less need to be productive to select into internal trade activities. In terms of policy implications, our results suggest that regional disparities matter also for international trade in that not only being in a denser area fosters productivity because of agglomeration economies, but it also allows firms to reach more easily international clients and suppliers so boosting participation into exporting and importing activities conditional on productivity.
Keywords: F14; R12; D24; 330; Firm-Level Dataset; Merging; BSD; FAME; VAT; Trade; Productivity; Markups; UK; Travel to Work Areas; Agglomeration Economies; International Trade Premia